Perbandingan Pertumbuhan Biji Kangkung (Ipomoea reptans Poir.) pada Berbagai Media Tanam Hidroponik Wick System dan Implementasinya Sebagai LKPD Biologi - Sainab, Sainab; Syakirah, Dewi; Sari, Arlinda Puspita (Journal of Health, Education, Economics, Science, and Technology, 2025)
Hydroponics is a technique for cultivating plants without using soil, instead utilizing water as the growing medium. This research aims to compare the growth of ground water spinach (Ipomoea reptans Poir.) using three different growing media (rockwool, husk charcoal, and cocopeat) with the wick hydroponic method. The parameters observed included plant height, number of leaves, fresh weight, and root length. The experimental design applied was a one-factor Randomized Block Design (RBD), with 3 treatments (rockwool, husk charcoal, and cocopeat) and 9 repetitions for each treatment. The results of this study show that differences in the three growing media at weeks 1, 5, and 6 had no significant effect on plant height, but they did have a significant effect at weeks 2, 3, and 4. Additionally, the differences in the three media at weeks 1, 2, 5, and 6 had no significant effect on the number of leaves, while weeks 3 and 4 showed significant effects. Notably, all three media had a significant effect on fresh weight, with cocopeat exhibiting the highest fresh weight, while no significant effect was observed on root length. These findings have been compiled into Student Worksheets (LKPD) for the 3.1 competency standard on growth and development in class XII biology.